Artificial Intelligence in the workplace : perceived knowledge, expectations and attitudes on university students and professionals - Canhestro, Teresa Sofia Pires (2020)
The presence of Artificial Intelligence (AI) in companies and in people’s daily lives is increasing fast, requiring an updated understanding of how people perceive its inclusion in the labour market. Because different backgrounds may be critical to such perception, the current study assessed the knowledge, expectations and attitudes that Portuguese university students and professionals in the areas of Psychology, Engineering, Economics and Management, Health and Humanities have regarding AI. A sample of 341 participants was collected, including 191 females and 119 males. The survey included questions from the AI@ 50 conference at Dartmouth College, the Survey of Expert Opinion (Müller & Bostrom, 2016), the Survey of Corporate Management and Economic Policy (Morikawa, 2017) and the Negative Attitudes Towards Robots Scale (NARS) (Nomura, Kanda & Suzuki, 2004), which assess, respectively, the temporal expectations of AI and the perceived impact AI may have on society, the perceived impact it may have on employment and, finally, attitudes toward intelligent robots at work. Results showed significant differences between groups from different scientific backgrounds: Engineering participants are more receptive to the inclusion of AI in work, when compared to the other groups. They are also more knowledgeable of robots and have a more positive attitude toward working with intelligent robots. Psychology participants are, right after Engineering participants, the ones who perceive themselves more favourably as to what they think they know about AI. Overall, results suggest that lack of information and a certain level of negative attitudes toward technology in the humanities group, and to some degree in all groups other that the engineering one, needs to be addressed by educational institutions, organization administrators and policy makers. This will facilitate an optimization of the AI technology for the specific requirements of different domains of human activity.